Portal Vein Obstruction in Pediatric Liver Transplant Patients: An Evaluation of Self‐Reported Management Practices - Lydia Sieben; Bader A. Alfares; Ruben H. deKleine; Barbara E. Wildhaber; Thomas Casswall; Greg Nowak; Martin Delle; Denise Aldrian; Valeria Berchtold; Georg F. Vogel; Piotr Kaliciński; Malgorzata Markiewicz‐Kijewska; et al. (Health Science Reports)
ABSTRACT Background and Aims Portal vein obstruction (PVO) is a known complication after pediatric liver transplantation (pLT). Effective management strategies are crucial in improving patient outcomes. This study investigated the various practice patterns related to PVO management to clarify the degree of consensus on the diverse facets of care involved in addressing PVO after pLT. Methods A self‐reported evaluation was conducted using a scanned, paper‐based survey among specialized pLT centers participating in the Portal vein Obstruction Revascularization Therapy After Liver transplantation (PORTAL) registry. The survey consisted of 30 questions covering the current practices regarding PVO, including experience, team composition, follow‐up and screening protocol, assessment criteria, postprocedural care, and radiologic follow‐up. Results The survey was returned by 25 centers (100%) from different regions worldwide. All centers used Doppler ultrasound (DUS) for PVO screening in the outpatient department. Noninvasive diagnostic criteria used during DUS assessment included anastomotic velocity (50%) and anastomotic‐to‐pre‐anastomotic velocity ratio (54%). Digital subtraction angiography was used by 79% of respondents to diagnose portal vein anastomosis stenosis, which led to diagnostic cutoff values including a narrowing of the visual aspect of the anastomosis of ≥ 50% (80%) and a pressure gradient ≥ 5 mmHg (50%). PTA was identified as a standard treatment for PVO. A remarkable heterogeneity was observed in postinterventional anticoagulation and surveillance protocols. Conclusions The care for PVO after pLT lacks standardization, resulting in substantial variation across healthcare centers. There is a need to establish a clear consensus on PVO management after pLT to guarantee optimal care. Trial Registration: NL9261.